Faktor-Faktor Penyebab Perceraian pada Pengadilan Agama Pariaman dengan Penerapan Metode Regresi Logistik Biner - Rahmawita Rahmawita; Atus Amadi Putra (UNIVERSITAS NEGERI PADANG, 2019)
Abstract — Divorce is the process of terminating a marriage. This research discusses the contributing factors of divorce by applying binary logistic regression methods at Religious Courts of Pariaman. The divorce lawsuit filed in Religious Court of Pariaman has undergone an increase in the last few years since 2014-2017 where this divorce case is improving more than 7000 cases per year. The factors used are husband’s age, wife’s age, husband’s education, wife’s education, there is third person, harshness, economic factors, unresponsibility, uncompatible. The population was all cases of divorce at Pariaman in January-February 2019 as many as 134 cases, which is using total sampling. Based on the result that the most dominant factor of divorce causes are husband’s education level and uncompatible. Keywords — Binary Logistic Regression, Divorce, Dominant Factors.